2014
DOI: 10.1590/s1677-5538.ibju.2014.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function in Male Patients with Metabolic Syndrome and Effective Parameters on Erectile Dysfunction

Abstract: ARTICLE INFO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
(30 reference statements)
0
10
0
2
Order By: Relevance
“…Gorgel et al conducted a study to investigate the relationship between metabolic syndrome and sexual function and effective parameters on erectile dysfunction (ED), and concluded that metabolic syndrome (including type 2 diabetes), smoking and obesity are potential risk factors for lack of sexual drive and satisfaction and ED [14].…”
Section: Discussionmentioning
confidence: 99%
“…Gorgel et al conducted a study to investigate the relationship between metabolic syndrome and sexual function and effective parameters on erectile dysfunction (ED), and concluded that metabolic syndrome (including type 2 diabetes), smoking and obesity are potential risk factors for lack of sexual drive and satisfaction and ED [14].…”
Section: Discussionmentioning
confidence: 99%
“…It is intuitive that the presence of a greater amount of periprostatic adipose tissue may increase the chance of injury to the neurovascular bundle. Obesity is also associated with the metabolic syndrome, the use of medications that may affect the quality of the erection, in addition to an endothelial inflammation and dysfunction (27). In the series of Wiltz et al the results were significantly worse after RARP for obese patients when compared to overweight (BMI≥25kgm 2 and <30kgm 2 ) and normal patients (BMI<25kgm 2 ), with 48.4%, 59.6% and 68.5% of potent patients after 12 months, and 55.9%, 78.9% and 80.3% after 24 months, respectively (p=0.02) (13).…”
Section: Discussionmentioning
confidence: 99%
“…A leptin/adiponektin arány eltolódása tüneteket nem okozó gyulladásos állapotot vált ki, amely IR-val és endothelfunkció-zavarral társul [13,29]. Megfigyelték, hogy a túlsúlyos és elhízott betegeknél a szexuális zavar gyakoribb, mint a soványakban, és a testtömegindex (BMI) növekedésével a zavar fokozódik [30,31]. Ennek hátterében neurobiológiai, hormonális, vascularis és mentális zavar állhat.…”
Section: Elhízásunclassified
“…Mivel a pénisz artériája vékonyabb a koszorúereknél, a szisztémás érkárosodás korábban vezet EDhoz, mint más CV betegséghez [38]. Az ED, a CV betegségek és a MS rizikótényezői megegyeznek egymással, és a MS komponensei közül a hasi elhízás látszik az ED fő kockázati tényezőjének [31]. Megfigyelték, hogy a MS kezelésével emelkedik a tesztoszteronszint, csökken az IR, és csökken az ED mértéke is [39].…”
Section: Férfiakban Előforduló Szexuális Funkciózavarunclassified